2021
DOI: 10.3389/fpls.2021.654676
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and RNA Interference Reveal GhGDH2 Regulating Cotton Resistance to Verticillium Wilt by JA and SA Signaling Pathways

Abstract: Verticillium wilt, caused by Verticillium dahliae, is one of the most damaging and widespread soil-borne cotton diseases. The molecular mechanisms underlying the cotton defense against V. dahliae remain largely elusive. Here, we compared the transcriptional differences between Upland cotton cultivars: one highly resistant (HR; Shidalukang 1) and one highly susceptible (HS; Junmian 1). This was done at multiple time points after V. dahliae inoculation, which identified 2010 and 1275 differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…WGCNA is widely used in transcriptome analyses, such as those performed in research involving growth and development regulation, environmental stress response, yield and quality formation, etc., especially for complex data models [ 81 , 82 , 83 ]. Some studies have mined and identified many functional genes by constructing a co-expression regulatory network [ 31 , 84 , 85 ]. Additionally, among the 43 candidate genes, DAO , which encodes a growth-hormone-oxidizing dioxygenase, was able to rapidly respond to nitrogen stress [ 86 ]; OsSultr1;1, the sulfate transporter protein, was regulated by nitrogen in a previous study [ 87 ]; Os08g0533300 was presumed to be ACR5 (accumulation and replication of chloroplasts 5), which has been significantly and positively correlated with plant growth [ 88 ]; and OsWNK6 may be functionally similar to OsWNK9 , which negatively regulated root elongation [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA is widely used in transcriptome analyses, such as those performed in research involving growth and development regulation, environmental stress response, yield and quality formation, etc., especially for complex data models [ 81 , 82 , 83 ]. Some studies have mined and identified many functional genes by constructing a co-expression regulatory network [ 31 , 84 , 85 ]. Additionally, among the 43 candidate genes, DAO , which encodes a growth-hormone-oxidizing dioxygenase, was able to rapidly respond to nitrogen stress [ 86 ]; OsSultr1;1, the sulfate transporter protein, was regulated by nitrogen in a previous study [ 87 ]; Os08g0533300 was presumed to be ACR5 (accumulation and replication of chloroplasts 5), which has been significantly and positively correlated with plant growth [ 88 ]; and OsWNK6 may be functionally similar to OsWNK9 , which negatively regulated root elongation [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungal recovery culture experiments were performed as previously described (Tang et al, 2019 ). The relative fungal biomass was determined by qPCR assay as previously reported (Xiong et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The roots of TRV:00 and GhTCP4-like plants 1 d after V. dahliae inoculation were used to measure total SA content by high-performance liquid chromatography-tandem mass spectrometry (HPLC/MS/MS) system (AB SCIEX QTRAP 4500, Foster, CA, USA) according to a previously described protocol (Xiong et al, 2021 ). In brief, approximately 200 mg of root samples from corresponding plants were ground to powder with liquid nitrogen and extracted twice with pre-cold 90% methanol overnight at 4°C, centrifuged at 13,000 rpm for 15 min, and the supernatant was dried with nitrogen using a speedvac and then dissolved in 300 μL of 100% methanol.…”
Section: Methodsmentioning
confidence: 99%
“…While pathogen recognition by plant receptors is a highly advanced field today (recently nicely summarized in Ngou et al, 2021 ), our understanding of xylem responses to compartmentalize pathogens mainly relies on anatomical studies of infected tissues and some recent proteomics and transcriptomics studies (Hu et al, 2019 ; Xiong et al, 2021 ). Another interesting study on V. longisporum infecting Arabidopsis plants showed that this soil‐borne fungal pathogen induces transdifferentiation of bundle sheath cells into functional xylem elements (Reusche et al, 2012 ).…”
Section: Wilt Pathogens and Their Impact On Xylemmentioning
confidence: 99%